Spinocerebellar Ataxia Type 2: Clinicogenetic Aspects, Mechanistic Insights, and Management Approaches - Velázquez-Pérez, Luis C.; Rodríguez-Labrada, Roberto; Fernandez-Ruiz, Juan (Frontiers in Neurology, 2017)
Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant cerebellar ataxia that occurs as a consequence of abnormal CAG expansions in the ATXN2 gene. Progressive clinical features result from the neurodegeneration of cerebellum and extra-cerebellar structures including the pons, the basal ganglia and the cerebral cortex. Clinical, electrophysiological and imaging approaches have been used to characterize the natural history of the disease, allowing its classification into four distinct stages, with special emphasis on the prodromal stage, which is characterized by a plethora of motor and non-motor features. Neuropathological investigations of brain tissue from SCA2 patients reveal a widespread involvement of multiple brain systems, mainly cerebellar and brainstem systems. Recent findings linking ataxin-2 intermediate expansions to other neurodegenerative diseases such as amyotrophic lateral sclerosis have provided insights into the ataxin-2-related toxicity mechanism in neurodegenerative diseases, and have raised new ethical challenges to molecular predictive diagnosis of SCA2. No effective neuroprotective therapies are currently available for SCA2 patients, but some therapeutic options such as neurorehabilitation and some emerging neuroprotective drugs have shown palliative benefits.